Evaluation of the use of magnetic sector secondary ion mass spectrometry to investigate 14C distribution in Magnox reactor core graphite. (2nd January 2018) - Payne, Liam; Heard, Peter J.; Scott, Thomas B.
Abstract: Large quantities of irradiated graphite will arise from the decommissioning of the UK's Magnox power stations. Irradiated graphite contains 14C as well as other longer lived radionuclides (e.g. 36Cl). The potential use of magnetic sector secondary ion mass spectrometry (MS-SIMS) to examine the distribution of the 14C within trepanned graphite samples from a Magnox nuclear power station has been investigated. This work indicates that the methodology proposed has the potential to be used to analyse irradiated graphite samples with preliminary results highlighting a possible 14C enrichment in the carbonaceous deposit found on a channel wall sample. 14C concentrations in samples without this deposit were below the limits of detection of the instrument. The methodology used for these determinations ensured that possible mass interferences between 14C species and oxygen-bearing or nitrogen-bearing species were eliminated from the analysis. Future work will utilize the methodology proposed in this work on a larger number of samples.